Estimating the cost of implementing a facility and community score card for maternal and newborn care service delivery in a rural district in Uganda - Ssebagereka, Anthony; Apolot, Rebecca Racheal; Nyachwo, Evelyne Baelvina; Ekirapa-Kiracho, Elizabeth (International Journal for Equity in Health, 2021)
This paper aimed at estimating the resources required to implement a community Score Card by a typical rural district health team in Uganda, as a mechanism for fostering accountability, utilization and quality of maternal and child healthcare service.
Keywords: #Reviews & Framing / Revisões e Organização; *indexed; *tagged; G - Rest of the World / Resto do Mundo; Health PEA; L - english / inglês; access to services / acesso a serviços; accountability / responsabilização; community scorecard (CSC) / cartão de pontuação comunitária (CPC); gender / género; health - maternal and child / saúde - materno-infantil; health / saúde; youth / juventude

Cidadania e Mudanças na Saúde e Educação em Moçambique: O Cartão de Pontuação Comunitária - Franco, Erika Lopez; Citizen Engagement Programme (CEP) (2017)
Este documento sumariza as aprendizagens feitas ao longo da implementação do Cartão de Pontuação Comunitária (CPC) no quadro do Programa Cidadania e Participação (CEP), o qual terminou em Dezembro de 2017. O CEP foi um programa de responsabilização social que tinha como objectivo final aumentar a influência dos cidadãos na melhoria da qualidade dos serviços de saúde e educação em Moçambique.
Accepted: 2018-04-13T12:59:17Z Publisher: (CEP) Citizen Engagement Programme / Cidadania e Participação
Keywords: G - Mozambique / Moçambique; G - north / norte; GP - Nampula; Health PEA; L - portuguese / português; Northern PEA; access to services / acesso a serviços; citizenship & participation / cidadania e participação; community scorecard (CSC) / cartão de pontuação comunitária (CPC); education / educação; health / saúde